Analisis Pemasaran Pinang Mentah Di PT. Timor Mitra Niaga Desa Wederok Kecamatan Weliman Kabupaten Malaka - Maria Sarice Nahak; Agustinus Nubatonis (Fakultas Pertanian, Universitas Timor, 2019)
Marketing is one of the conditions for progressive agriculture development. weakness in the agricultural development system in developing countries including Indonesia is the lack of attention in the field of marketing. The objectives of this study are: 1) to find out the marketing of raw areca nut, 2) to determine the marketing functions, 3) to determine the margin of raw areca marketing in Timor Mitra Niaga Wederok Village, Weliman District, Malacca District. This research was conducted in April-May 2018 in Timor Mitra Niaga Wederok Village, Weliman District, Malacca District. Sampling using the Snowball Sampling method. The data used are primary data and secondary data. Data analysis methods are descriptive analysis and marketing margin analysis. The research results obtained that the marketing channel of raw areca nuts from producers directly to consumers and producers also market raw areca nuts through the retailer's sword. The marketing functions performed by retailers are the purchasing function, sales function, transportation function, storage function, standardization, and grading function, capital function, risk management function and market information function, while raw areca producers perform sales function, standardization and grading function, and risk management functions. Raw areca marketing margin of Rp 5,000 / kg or 50% of the price paid by consumers.